Research Progress and Key Scientific Issues Impacting Urban Agriculture Functional Transformation for Urban-Rural Integration - Yang Ren; Lin Yuancheng (Redai dili, 2024)
Under the auspices of the national strategies for urban-rural integration and rural revitalization, a focus on the functional evolution and spatial reorganization mechanisms of urban agriculture is of great theoretical and practical significance. This paper analyzes research progress in urban agriculture functional transformation and presents key scientific issues in urgent need of attention in future research. This paper aims to promote high-quality, ecologically sound development of urban agriculture and provides a scientific basis for integrated development of urban and rural areas. We have found that: 1) Research into urban agriculture functional transformation mainly focuses on evaluation and division of urban agriculture development transformation into type models, including multi-functional transformation and sustainable development of urban agriculture, spatial organization and production organization pathways of urban agriculture, land use and bidding mechanisms applied to urban agriculture development, and problems arising from urban agriculture and its multi-dimensional effects. At present, research related to the functional transformation of urban agriculture is guided by the theories of agricultural development, agricultural multi-functionality, and agricultural product demand, focusing on land alienation, ownership security, and diversification of agricultural production subjects in the process of urbanization. 2) The development of urban agriculture presents complex characteristics (i.e., it is multi-subject, multi-linkage, and multi-objective), and coordination of mixed social relations based on the demands of different stakeholders can also pose difficulties. The process and results of the cooperative game of urban agricultural space rental competition and subject interests exert crucial impacts on the restructuring of urban agricultural production system and spatial organization. The dynamic mechanisms of functional evolution and spatial reorganization of regional urban agriculture systems need to be studied. An urgent need exists to strengthen research into land bidding, land tenure, and related stakeholders in urban agriculture development from the perspective of regional systems. It is necessary to clarify the basic and dominant factors influencing the evolution of urban agriculture systems based on different scales, subjects, and perspectives and to elucidate the rent competition mechanism underlying spatial reorganization and ecological and environmental effects. 3) Future research needs to solve key scientific issues regarding three aspects of urban agriculture functional transformation. First, from the perspective of the rural-urban continuum, to clarify the interaction linkage and coupling mechanism between endogenous and external forces driving regional functional evolution in urban agricultural systems. Second, to reveal the key mechanism of spatial restructuring of regional urban agricultural systems and clarify synergies among stakeholders and the logic of land bidding. Third, based on the ecological and environmental impacts of the functional evolution of regional urban agriculture systems and spatial reorganization, comparative studies on the ecological impact of regional functional transformation of agricultural systems at different locations on urban-rural spatial gradient transects are needed.